Upaya Dinas Perpustakaan Kabupaten Hulu Sungai Utara dalam Meningkatkan Layanan Anak Periode Tahun 2023 - Fatimah, Siti; Mufid, Moh. (Jurnal Pustaka Ilmiah, 2023)
This study aims to determine efforts to improve children's services at the Library Service of Hulu Sungai Utara in 2023. The research method is a qualitative descriptive approach. Data collection techniques used literature studies and interviews with the head and librarian of the North Hulu Sungai District Library Service. The results of the study show that in an effort to improve children's services in 2023, the Library Service of Hulu Sungai Utara Regency has made a lot of improvements in the availability of various elements of children's services, namely in terms of collections, facilities,and types of children's services that are compatible with child's needs and age. Efforts to improve it by providing computers to browse catalog data, computers for visitors, locker rooms, lobby rooms, reading corners as well as new games such as swings, ball baths, and others. Librarians/service staff at the Library Service of Hulu Sungai Utara District do not yet have children's librarians, namely librarians specifically for children's services. Efforts made are holding special programs as well as promotions directly and indirectly.